Оpportunities for utilizing tourism potential in the sustainable development of small arid-climate areas (the case of Кattakurgan district, Uzbekistan) - Avezov, Mukhriddin; Elmurotova, Aziza (Geography and Sustainable Development, 2026)
This scientific article examines the concepts of small-area development, highlighting the importance of tourism in fostering sustainable economic growth, particularly in small arid regions. Based on the proposed theories, the tourism potential of the Kattakurgan district of Samarkand region has been analyzed in the context of sustainable development through alternative tourism. Furthermore, given the arid climate, NDVI maps reflecting vegetation density were developed and analyzed to properly manage tourist flows. The study also reviews the multi-year average monthly air temperature, relative humidity, and water vapor pressure variations in order to assess climate comfort for tourists, with specific recommendations provided. From the perspective of sustainable tourism development, a schematic map for organizing tourism activities was designed using the multi-year average monthly water temperatures, underwater geomorphology, and shoreline dynamics of the Kattakurgan Reservoir. In addition, the potential of the Kattakurgan district’s tourism resources was assessed through a SWOT analysis, and conclusions were drawn accordingly.